Interface Between Clarity PPM and External System- SAP PS - Asha D, Dr. B S Kariyappa (International Journal of Advanced Science and Technology, 2020)
Clarity Project and Portfolio Management (CA PPM) is a platform that empowers to manage the life cycle of innovative projects and investment planning. SAP PS is a financial system, which provides invoice billing, cash flow monitoring and integration with other systems, SAP PS (System Applications Products Project Structure) is capable of managing both technical and commercial aspects of a project. In Clarity PPM, project, task, timesheet creation, and integration with SAP (Systems Applications Products) multiple financial systems are executed, projects/programs are given to clarity by planisware to perform interface between clarity and other external systems. Clarity manages the project, resource, and task allocates team members to the project. Non-financial data is sent to SAP and financial data is reported back to clarity. The master data analysis, tracking of AIP's (Application Programming Interface) and risk assessment is done at clarity. The cost calculated for the project interfaced to SAP PS is 4000 Euro, actual hours × billing rate gives cost estimate. Qlikview gives the overall analysis for all the data and it is an end-reporting tool. This paper illustrates real-time integration between CA PPM and SAP PS. SQL, NoSQL, java scripting, and GEL scripts software has used for coding. Oracle database stores all the data's in the data table, middleware (OnePO/ESB) web service such as SOPA (Simple Object Access Protocol) tools has used for the development of an interface between clarity and SAP.